(untitled) (Indian Journal of Public Health Research & Development, 2023)
Background: Advocates practise for long hours with hectic work schedules. Work pressure, changing legal landscapes, uncertainty of legal cases is a great challenge to lawyers. They are unable to concentrate on their health related activities. Physical inactivity causes obesity leading to risk of hypertension. In view of above issues one of the main objectives of the study is to evaluate the relationship between physical activity, Body Mass Index and hypertension among practising advocates. Methods: A sample of 300 practising advocates at Madurai district court was selected by simple random sampling method. Data was collected using structured interview schedule and analysed using SPSS. Results: Nearly 90% advocates with raised body mass index were hypertensives and 68.42% advocates with inadequate physical activity developed hypertension. The difference of observation was found to be statistically significant (p=0.0000). Conclusions: Practice of health fitness activities amidst busy schedule and Self- care management modifies the effect of Body Mass Index on hypertension risk.